Characteristics of the State: Basic Concepts in Modern National Legal Science - S. Yu. Pavlov (Сибирское юридическое обозрение, 2018)
The article is devoted to the definition of the concept of the state through its features. The Author notes that by this time the universal definition of the state is not formulated in modern Russian legal science. To confirm his point of view, the Author cites the main concepts of the state from the works of Russian scientists, paying special attention to its features. As a result of the analysis, the Author identifies two basic meanings of the concept of the state, which include ideas about the state as an apparatus of state power and as some kind of state-organized community. It is emphasized that the discrepancies in the interpretation of the essence of the state are explained by which of the signs of the state receive the status of primary, and which of them are derived. According to the Author, when defining the concept of a state, it is necessary to consider the entire set of features that will allow the development of a universal definition.